2016
DOI: 10.1016/j.jaci.2016.08.043
|View full text |Cite
|
Sign up to set email alerts
|

A health care navigation tool assesses asthma self-management and health literacy

Abstract: BACKGROUND Self-management of moderate/severe asthma depends upon patients’ ability to: 1) navigate (access health care to obtain diagnoses and treatment), 2) use inhaled corticosteroids (ICS) properly, and 3) understand ICS function. OBJECTIVE To test whether navigation skills (medication recall, knowledge of copay requirements ability to provide information needed for a medical visit about a persistent cough unresponsive to medication), are related to other self-management skills and to health literacy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
(41 reference statements)
0
10
0
Order By: Relevance
“…Whilst research into the effects of social media is still relatively new, some studies have identified negative psychological consequences. For example, using Facebook has been found to have a negative association with well-being [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ] and a positive association with depression [ 8 ]. Social anxiety levels have also been shown to be higher in people who spend more time using Facebook and for those who use Facebook passively (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst research into the effects of social media is still relatively new, some studies have identified negative psychological consequences. For example, using Facebook has been found to have a negative association with well-being [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ] and a positive association with depression [ 8 ]. Social anxiety levels have also been shown to be higher in people who spend more time using Facebook and for those who use Facebook passively (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We developed and validated a questionnaire, Navigating Ability , which focuses on specific tasks promoted in the PAI protocol. 78 The instrument was validated on 250 patients (Cronbach’s alpha=0.54), consistent with several concepts being measured by the instrument (i.e. multidimensional).…”
Section: Hap2 Protocolmentioning
confidence: 73%
“…5355 We also hypothesize that patient satisfaction with communication with providers should improve with the PAI. Finally, we have developed and validated a questionnaire, Navigating Ability 56 that measures the ability to access health care and to obtain diagnoses and treatment that is promoted by the PAI.…”
Section: Methodsmentioning
confidence: 99%
“…In these studies, navigation or—in the words of Gui and colleagues [ 46 ] (p. 2)—“navigational competence” is primarily conceptualized as the knowledge and skills needed to find and use suitable services in the health care system. These skills are linked to information and experience as a source of knowledge and were conceptualized and examined as a potential outcome of health literacy [ 43 , 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…For the latter there are only a few studies addressing health literacy in terms of navigation [28,41,42]. Most studies tend to focus more on the skills and processes required to find one's way around the health care system [9,[43][44][45][46]. In these studies, navigation or-in the words of Gui and colleagues [46] (p. 2)-"navigational competence" is primarily conceptualized as the knowledge and skills needed to find and use suitable services in the Int.…”
Section: Scoping Literature Reviewmentioning
confidence: 99%